The Implications of Leadership Style, Human Resources Practices, and Organizational Culture on Employee Performance in PT Kansai Prakarsa Coatings - Septian Anggra Setiawan (Bina Nusantara University, 2019)
This research analyzed the relationship between leadership style, Human Resources (HR) practices, and organizational culture on employee performance in PT Kansai Prakarsa Coatings in Indonesia. This research was expected to find the information related to what factors greatly affected employee performance and be an input for foreign paint manufacture to set up paint companies in Indonesia. The sample was 230 from 650 employees, chosen by stratified random sampling from each division to get a representing answer. The used analysis model was descriptive and path analysis. The result shows that there is a negative significant between leadership style and organizational culture to employee performance. On the other hand, there is a significant positive relationship between HR practices and employee performance.